The potential of the digital environment in the training of specialists in social work - E. Litvinova; O. Afanasyeva (Вестник Северо-Кавказского федерального университета)
The article is devoted to the problems of digitalization of social education. The authors analyzed the positive and negative effects of digitalization of the activities of social work specialists, its impact on the system of professional training of social sphere personnel. The problems of social education are highlighted and possible ways of solving them using the potential of the digital environment are characterized. The possibilities of the digital environment for all subjects of the educational process are considered, the advantages of digitalization in the training of specialists in social work are specified. An overview of the problems of the formation of the digital environment at the level of an educational organization and measures to overcome them is presented.